Stability Analysis for Multiple Voltage Source Converters Connected at a Bus - Ghosh, Arindam; Ledwich, G.; zare, F.; Majumder, R. (International Academy, Research, and Industry Association ( IARIA ), 2011)
This paper develops a tool for the stability analysis when multiple voltage controlled converters are connected to a distribution bus. In particular, the analysis is applicable to voltage source converters (VSCs) and has been extended to consider current control as well as voltage control. It is assumed that each VSC is controlled by a state feedback linear quadratic regulator (LQR) based switching design. A suitable model of the converter is first developed by including the state feedback gains. The model is then extended to incorporate parallel operation of two VSCs, connected to a bus. To consider autonomous operation, the power sharing arrangements without any explicit communication, i.e., droopcontrollers are incorporated in the model. Finally, a linearized model of the system is developed for Eigen analysis. It has been shown that the system response predicted by the developed model matches PSCAD simulation results very closely, thus confirming that the model developed can be used as an analytical tool.